Influence Of Altruism, Biospheric, Egoistic, And Product Quality Values On Energy-Efficient Home Appliances Purchase Intention Among Millennials And Gen Z - Bertha Rastika (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study examines how personal values—altruistic, biospheric, egoistic—and perceptions of product quality influence the intention to purchase energy-efficient home appliances (eeha).survey data were collected from 221 prospective indonesian consumers and analyzed using structural equation modeling (sem). Findings: by incorporating egoistic values focused on self-benefit into the existing framework of personal values, this research offers a broader view of the motivations behind environmentally conscious purchasing. It reveals how both self-centered and pro-social values contribute to consumers’ interest in eeha. Originality/value: building on the value-based model proposed by bhardwaj et al. (2023), this study introduces egoistic values as an additional dimension. While past studies often overlook self-enhancing motives, this research addresses that gap and focuses specifically on the growing importance of eeha in sustainable living. Practical implications: findings suggest that social influence is a key driver of eeha purchase intention, highlighting the effectiveness of campaigns involving influencers and eco-communities. Perceived behavioral control also plays a crucial role, emphasizing the need to improve access, affordability, and consumer knowledge. Marketing should emphasize environmental benefits and product performance, as these factors significantly impact positive attitudes, while egoistic appeals are less effective.